If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(4y + -6y) + 5(13y + 1) = 9 Combine like terms: 4y + -6y = -2y 11(-2y) + 5(13y + 1) = 9 Remove parenthesis around (-2y) 11 * -2y + 5(13y + 1) = 9 Multiply 11 * -2 -22y + 5(13y + 1) = 9 Reorder the terms: -22y + 5(1 + 13y) = 9 -22y + (1 * 5 + 13y * 5) = 9 -22y + (5 + 65y) = 9 Reorder the terms: 5 + -22y + 65y = 9 Combine like terms: -22y + 65y = 43y 5 + 43y = 9 Solving 5 + 43y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 43y = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 43y = 9 + -5 43y = 9 + -5 Combine like terms: 9 + -5 = 4 43y = 4 Divide each side by '43'. y = 0.09302325581 Simplifying y = 0.09302325581
| U/745=-60 | | 0.25(t+5)=22 | | x^2-6x+8y-47=0 | | 1.25(x+8)=4 | | 5+2(b-7)=-6 | | 2x-10/25-x^2= | | -9(3f-5)= | | a(a-5)=-6 | | 60-15i/(17-8i) | | 2/7=(0.6)^2x | | 4/10=x/100 | | 2x-5=-2x+7 | | 10a^5b^4/2a^2b^3= | | 3x+x-2+8=3x+x | | -6-7(9b-8)= | | 7/10=n/990 | | -3(5x-6)=93 | | 4(a+3)=10 | | 3/5z=-12 | | 7log(3x)=21 | | 12-2y=14 | | 2y-5=3y-10 | | 1(3x-4)-2(x-5)=4 | | 3x+7=-x-5 | | (3x+5)-(13x)=25 | | 7w+5(-8w-9)= | | 5u/9=20 | | 4x-1+x+8+5y+2=180 | | X/3.2=2.39 | | 5.3x=23.2 | | -2(4x-5)+3x=-6x-11 | | 500/80=300/n |